Pengawasan Terhadap Penyelenggaraan Pemilihan Kepala Desa - Tuasalamony, Muhammad Zarkasyi; Pattipawae, Dezonda Rosiana; Nirahua, Graciano (Faculty of Law Universitas Pattimura, 2024)
The election of the Village Head is direct, general, free, secret, honest and fair. So, in order to realize democratic village head elections, supervisory institutions are required to carry out supervision in accordance with their authority in village head elections. However, there were findings of violations in the implementation of village head elections, namely procedural inconsistencies in receiving registration documents for prospective village head candidates and a number of voter lists were still considered invalid. This research raises two problems, namely how to supervise the implementation of village head elections and the form of supervision of village head elections. The research method used in this writing is a normative juridical research method with a statutory approach and a conceptual approach. The results of this research can be concluded that supervision of democratic Village Head elections can be carried out in accordance with the guidelines for simultaneous village head elections through a monitoring mechanism, in this case the election supervisor checks the completeness, correctness, accuracy and validity of documents as well as the number of vote counts which are the object of supervision. at every stage of holding village elections, and the most effective form of supervision applied in holding Village Head elections is the form of repressive supervision in the form of inquiry and investigation, temporary suspension of vote counting, reporting and follow-up, as well as confiscation and freezing of vote counting results.